Tick genomics - coming of age - Nene, Vishvanath M. (Frontiers Media, 2009)
Many challenges face tick genomics. Ticks have large genomes and their estimated sizes vary from 1.04~7.1 x10(9) bp, about one third to over two times the size of the human genome. Karyotype studies have revealed a range in chromosome number and the sex determining system seems to be primarily driven by a XY or a XO format. Re-association hybridization kinetics indicates that the bulk of the tick genome consists of repetitive sequences and only 30~35% of the genome consists of low copy number sequences. The former remain poorly characterized and most of what we know about the latter has been driven by gene discovery projects via generation of expressed sequence tags (ESTs). However, large scale EST data (>10,000 ESTs) are available for only three tick species. The only whole genome sequencing project for ticks is that on Ixodes scapularis, the primary tick vector of medical importance in the United States. Nevertheless, important advances are being made in developing genomics tools and these will stimulate research in tick and vector biology.